PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA NELAYAN TRADISIONAL DI KECAMATAN TELUK PANDAN KABUPATEN PESAWARAN - Marina Ulva; Fembriarti Erry Prasmatiwi; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This research is to analyze income obtained by traditional fishermen from fish catching, their householdincome, the level of welfare, and factors influencing the welfare level of traditional fishermen households inTeluk Pandan District. This study was conducted in Sukajaya Lempasing Village, Teluk Pandan District,Pesawaran Regency with a survey method. Respondents were 48 traditional fishermen who used netfish andwere selected using simple random sampling method. Household income consists of on farm, off-farm, andnon-farm. Household welfare level is analyzed by Central Agency on Statistics 2014 and the Sajogyo 1997criteria. The factors influencing welfare are determined using binary logistic regression. The resultsshowed that the income obtained by fishermen from fish catches in the western season was Rp6,570,375, inthe eastem season was Rp25,452,214, and in the normal season was Rp15,229,771. The contribution of fishcatches income (on farm) was 91.01 percent, the contribution of bussines income in the agricultural sectoroutside the fish catches (off farm) was 5.55 percent, and the contribution of business outside the agriculturalsector (non-farm) was 3.60 percent. As many as 68.77percent of the traditional fishermen households areclassified as unprosperous yet and 31.25 percent are prosperous based on Central agency on Statistics 2014criteria. The factors influencing the welfare of traditional fishermen households were the level of educationand income.Key words: income, traditional fishermen, welfare.